Survei Kondisi Fisik Atlit Futsal SMBR FC (Semen Baturaja Futsal Club) - Masagus Amarthyo Tanzilalaziiz; Endi Riyoko; Puput Sekar Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the Physical Condition of SMBR FC (Semen Baturaja Futsal Club) Futsal Athletes. The sample in this study were SMBR FC (Semen Baturaja Futsal Club) futsal athletes totaling 10 people. This type of research is quantitative descriptive research, the instrument used consists of balke test, vertical jump test, sprint test, and shuttle run test. Based on data processing carried out with a statistical system, athletes who get the perfect category are 3 people with a percentage (30%), a very good category is 2 people with a percentage (20%), a good category is 4 people with a percentage (40%), a sufficient category is 1 person with a percentage (10%), while the category is lacking none with a percentage (0%). Thus, the physical condition of SMBR FC (Semen Baturaja Futsal Club) futsal athletes can be categorized as good.